2020
DOI: 10.1177/1759720x20975904
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase subtilisin/kexin type 9 is related to disease activity and damage in patients with systemic erythematosus lupus

Abstract: Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a serine protease that regulates cholesterol metabolism through low-density lipoprotein receptor degradation and that has been linked to cardiovascular (CV) disease. The purpose of the present study was to examine whether PCSK9 levels are disrupted compared with controls in patients with systemic lupus erythematosus (SLE). We additionally sought to establish whether PCSK9 is related to both the abnormalities in the lipid profile and to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…Patients with systemic lupus erythematosus (SLE) have a high prevalence of premature CVD ( 7 ). Besides, they exhibit changes in serum lipids and lipoproteins ( 8 , 9 ). Although studies have reported a variety of modifications of lipid metabolism in patients with SLE, this alteration appears to be characterized by low HDL cholesterol, high triglycerides, and normal or elevated LDL cholesterol ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with systemic lupus erythematosus (SLE) have a high prevalence of premature CVD ( 7 ). Besides, they exhibit changes in serum lipids and lipoproteins ( 8 , 9 ). Although studies have reported a variety of modifications of lipid metabolism in patients with SLE, this alteration appears to be characterized by low HDL cholesterol, high triglycerides, and normal or elevated LDL cholesterol ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) has been associated with increased cardiovascular (CV) disease [ 1 ] and altered lipid profile [ 2 ]. Although the exact mechanisms by which this occurs are unknown, it is believed that the inflammation that accompanies the disease is responsible for dyslipidemia and the increased CV risk that occurs in patients with SLE [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence showing that chronic inflammation impairs and alters lipoprotein metabolism and causes a variety of changes in plasma lipid and lipoprotein concentrations. This has been widely described in diseases such as systemic lupus erythematosus [ 14 , 15 ] and rheumatoid arthritis [ 16 ]. In addition, LPL is known to be upregulated in patients with systemic lupus erythematosus [ 17 ].…”
Section: Discussionmentioning
confidence: 99%